2005
DOI: 10.1007/s00221-005-2365-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulations among the alerting, orienting and executive control networks

Abstract: This paper reports a series of experiments that were carried out in order to study the attentional system. Three networks make up this system, and each of them specializes in particular processes. The executive control network specializes in control processes, such as conflict resolution or detection of errors; the orienting network directs the processing system to the source of input and enhances its processing; the alerting network prepares the system for a fast response by maintaining an adequate level of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

48
320
9
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 265 publications
(388 citation statements)
references
References 34 publications
48
320
9
11
Order By: Relevance
“…This is consistent with recent research showing that the three attentional subsystems are able to work together to influence behavior. Research has shown that the alerting network inhibits executive control, whereas the orienting network enhances executive control (Callejas, Lupiáñez, Funes, et al, 2005;Callejas, Lupiáñez, & Tudela, 2004;Fan, Gu, et al, 2009) and the alerting network modulates orienting effects (Fuentes & Campoy, 2008). Furthermore, there is substantial functional overlap across the different neural networks (Fan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is consistent with recent research showing that the three attentional subsystems are able to work together to influence behavior. Research has shown that the alerting network inhibits executive control, whereas the orienting network enhances executive control (Callejas, Lupiáñez, Funes, et al, 2005;Callejas, Lupiáñez, & Tudela, 2004;Fan, Gu, et al, 2009) and the alerting network modulates orienting effects (Fuentes & Campoy, 2008). Furthermore, there is substantial functional overlap across the different neural networks (Fan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They did, however, report a significant interaction between cue condition and flanker type, which implies that attention networks are not entirely independent (Fan, McCandliss, Sommer, et al, 2002). In order to investigate potential interactions across attention networks, Callejas and colleagues (Callejas, Lupiáñez, Funes, & Tudela, 2005;Callejas, Lupiáñez, & Tudela, 2004) modified Fan's task by including a new alerting stimulus: a short-duration high-frequency tone. This modification enabled the researchers to measure each network independently and to quantify the effect of one network on the other two networks.…”
mentioning
confidence: 99%
See 3 more Smart Citations